Exploring alkaline routes for production of TEOS-based consolidants for carbonate stones using amine catalysts. (15th February 2021) - Rodrigues, Alexandra; Sena da Fonseca, Bruno; Ferreira Pinto, Ana Paula; Piçarra, Susana; Montemor, M. Fátima
Abstract : TEOS-based sols following basic catalysis routes were explored and showed high potential and important advantages for consolidation of soft limestone. Abstract : This work aims at developing TEOS-based sols for the consolidation of carbonate stones, following basic catalysis routes, which have been scarcely explored. The influence of the alkaline media in the sol–gel chemistry is a well-known phenomenon and has been considered a drawback. This work demonstrates that under controlled and well-selected conditions, there is high potential on this novel approach and important advantages. Basic catalysts containing NH-goups (ammonia, n -octylamine, diethanolamine and triethanolamine) were used in the production of TEOS-based sols. The role of the different amines on the consolidation efficacy of the final gels was then investigated. The development of new TEOS-based solutions with potential consolidation efficacy has been achieved by tailoring several parameters ( e.g. precursor/catalyst and precursor/solvent ratios). Optimisation of parameters and modification of the silica structure with different amines allowed us to produce a set of consolidants for carbonate stones. The morphology and structure of xerogels were characterised, sol behaviour was studied after their blending with calcite powder, as well as after their application on soft limestone samples. Cohesive monoliths of calcite powder were obtained, and significant and uniform drilling resistance increments in treated stones were achieved using sols with different TEOS : ethanol : catalyst ratios.